Nutrition and the state of the intestinal microflora in the formation of the metabolic syndrome - V. P. Patrakeeva; V. A. Shtaborov (Ожирение и метаболизм, 2023)
The literature review presents the results of modern studies of the relationship between diet and intestinal microbiota in the regulation of metabolic disorders. Metabolic syndrome, which is a symptom complex that combines abdominal obesity, insulin resistance, hyperglycemia, dyslipidemia and arterial hypertension, remains an important problem, being a risk factor for cardiovascular, neurodegenerative, oncological diseases and the development of type 2 diabetes mellitus. Although the pathogenesis of the metabolic syndrome has not yet been fully elucidated, it is known that visceral obesity and its associated complications, such as dyslipidemia and increased levels of pro-inflammatory cytokines, play a central role. The article presents data on the impact of the consumption of certain food products, the inclusion of plant biologically active substances (flavonoids, polyphenols, etc.) in the diet, as well as the use of elimination diets with the exclusion of carbohydrates or fats from the diet, on reducing the risk of cardiovascular accidents, levels of fasting glucose, total cholesterol, LDL, triglycerides, C-reactive protein, leptin, insulin, reduction in body weight and waist circumference, reduction in the level of circulating endotoxins and changes in the activity of immunocompetent cells. Data are presented on the possible influence of the intestinal microbiota in maintaining inflammation and the formation of degenerative changes in the body. The role of changes in the ratio of the levels of pathogenic microflora, bifidobacteria and lactobacilli in the formation of a pathological condition is shown.